2022
DOI: 10.1017/s0025100322000044
|View full text |Cite
|
Sign up to set email alerts
|

Northern Tosk Albanian

Abstract: Albanian (endonym: Shqip; Glotto: alba1268) is an Indo-European language which has been suggested to form an independent branch of the Indo-European family since the middle of the nineteenth century (Bopp 1855, Pedersen 1897, Çabej 1976). Though the origin of the language has been debated, the prevailing opinion in the literature is that it is a descendant of Illyrian (Hetzer 1995). Albanian is currently spoken by around 6–7 million people (Rusakov 2017: 552; Curtis 2018: 1800), the majority of whom live in Al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Orthographically, /c/ is represented as <q> and /tS/ is represented as <ç>. Beci (2004) and other traditional phonetic manuscripts in Albanology (i.e., Dodi 2004;Memushaj 2011) consider /c/ to be a palatal plosive, as transcribed here (but see Lowman (1932) and Coretta et al (2021), who argue that /c/ is an alveo-palatal affricate). The phoneme /tS/ is a relatively common sound in the languages of the world, and, as in these languages, in Albanian, also, it is often described as a palato-alveolar affricate (Lowman 1932;Beci 2004).…”
Section: Albanian Languagementioning
confidence: 73%
See 1 more Smart Citation
“…Orthographically, /c/ is represented as <q> and /tS/ is represented as <ç>. Beci (2004) and other traditional phonetic manuscripts in Albanology (i.e., Dodi 2004;Memushaj 2011) consider /c/ to be a palatal plosive, as transcribed here (but see Lowman (1932) and Coretta et al (2021), who argue that /c/ is an alveo-palatal affricate). The phoneme /tS/ is a relatively common sound in the languages of the world, and, as in these languages, in Albanian, also, it is often described as a palato-alveolar affricate (Lowman 1932;Beci 2004).…”
Section: Albanian Languagementioning
confidence: 73%
“…For our study, we were interested in considering this potential sound change (see the recent study by Coretta et al (2021), who specify that <q> is actually an affricate). It is often proposed that sound changes are led by younger female speakers (Milroy and Milroy 1985;Labov 1990;Williams and Kerswill 1999;Fridland 2008;Harrington et al 2008;Lewis et al 2019) so in examining our data, we considered it relevant to examine whether this sound change might have been led by younger females as well.…”
Section: Albanian Languagementioning
confidence: 99%
“…However, /@/ presents great variation across different speakers and contexts. It has been suggested that it comprises an open-mid unrounded vowel, phonologically transcribed as /3/ [58]. In addition, vowels /e/ and /o/ exhibit free variation, occasionally manifesting as more open-mid sounds [E] and [O] [59].…”
Section: Greek and Albanian Vowel Systemsmentioning
confidence: 99%
“…Unlike neighbouring Balkan countries, where linguistic maps are readily available [33][34][35][36][37], the dialectal varieties of modern Greek (especially those of the mainland), although well-studied at the regional level, have rarely been researched under the lens of comparative historical linguistics, nor have they been mapped [38]. As a result, the boundaries of Greek dialectal varieties, their phylogenetic relationships, their contact with different idiomatic forms of Greek or other languages, as well as the historical processes that shaped their evolution and distribution, have often remained elusive [38].…”
Section: Introductionmentioning
confidence: 99%